POST AND PRE-INDEPENDENCE BEVERAGES IN INDIA AND THEIR IMPACT ON HEALTH - Bedi, Siddharth (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Objective Beverages are consumed by the majority of the population throughout the world. Traditionally, based on geographical location and tradition, beverages are formed. Due to the advancement of brand-based soft drinks, traditional beverages are not known in the modern era. This paper is aimed at evaluating the impact of beverages consumption on the health of the country. It will try to explain the difference in the post and pre-independence health scenarios of the country. Methods To achieve these objectives, this study will analyze the secondary data on the impact of beverages on the country's health. In order to provide a comprehensive picture, this study will also look at the economic contribution of the industry. This examination provides information about traditional beverages and their health impacts. After the independence lot of soft drinks have emerged, this research intended to critically examine the health impact of traditional beverages and soft drinks. It is evaluated based on research articles about tradition. Results The result of the analysis shows that traditional beverages exhibit significant health benefits rather than soft drinks. It also shows that this industry has contributed significantly to the GDP of the County. Conclusion The beverages industry needs to incorporate good innovation and reformulation for improving nutrient and phytonutrient profiles. With technological advancement, products need to concentrate on nutritional benefits with reduced sugar, artificial ingredients, and increased nutrient density. The nutrients can be improved with the composition of dietary, fruit, and vegetable juices to develop nutrients.